Making healthy places designing and building for health, well-being, and sustainability - Dannenberg, Andrew L.; Frumkin, Howard; Jackson, Richard 1945- (Island Press, 2011)
The environment that we construct affects both humans and our natural world in myriad ways. There is a pressing need to create healthy places and to reduce the health threats inherent in places already built. However, there has been little awareness of the adverse effects of what we have constructed-or the positive benefits of well designed built environments.   This book provides a far-reaching follow-up to the pathbreaking Urban Sprawl and Public Health, published in 2004. That book sparked a range of inquiries into the connections between constructed environments, particularly cities and suburbs, and the health of residents, especially humans. Since then, numerous studies have extended and refined the book's research and reporting. Making Healthy Places offers a fresh and comprehensive look at this vital subject today.   There is no other book with the depth, breadth, vision, and accessibility that this book offers. In addition to being of particular interest to undergraduate and graduate students in public health and urban planning, it will be essential reading for public health officials, planners, architects, landscape architects, environmentalists, and all those who care about the design of their communities.   Like a well-trained doctor, Making Healthy Places presents a diagnosis of-and offers treatment for-problems related to the built environment. Drawing on the latest scientific evidence, with contributions from experts in a range of fields, it imparts a wealth of practical information, with an emphasis on demonstrated and promising solutions to commonly occurring problems.